Relationship between selected factors on barriers of transfer of training towards the effectiveness of the training program - Toh, Shu Lim; Ahmad, Rusli; Bujang, Sopian (2008)
This study aims to identify the relationship between selected factors on barriers of transfer of training towards the effective of training program. There are five independent variables being studied, which are learning organization, trainee motivation, training environment, management support and peer support. The dependent variable refers to the effectiveness of training program. Convenience sampling and questionnaire was used to collect the data which involving 100 respondents as a sample of the study. Four out of five barriers of transfer (learning organization, trainee motivation, training environment and peer support) were found significantly related to training effectiveness. Training environment found to affect training effectiveness the most. This research is important to overcome barriers of transfer of training in the work place. The organization may use the outcome of the study to improve the conditions, environment and facilities of the training program so that the training program is effective in the future. It is recommended that future researchers may include larger sample and study different variables when conducting their research in the related field.